NOTES ON THE ANTHOLOGIA LATINA. - Watt, W. S. (Harvard Studies in Classical Philology, 2003)
Discusses the highlights of the book "I Anthologia Latina: Carmina in codicibus scripta. Fasc. 1. Libri Salmasiani aliorumque carmina." Preface to the summaries of the books of "Aeneid"; Alternative accounts of the origin of the red colour; Analysis of a closing couplet of a short piece about a bird which is brought down by the weight of its drenched wings.